2017
DOI: 10.17306/j.afs.2017.0442
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of obesity complications

Abstract: Intensive research is currently being performed into the genetic background of excess body mass complications such as diabetes, cardiovascular disorders, especially atherosclerosis and coronary heart disease. Chronic inflammation is an important process in the pathogenesis of obesity, wherein there is an aberrant expression of genes encoding adipokines. Visceral tissue is characterized by a higher expression and secretion of interleukin-8, interleukin-1ß and plasminogen activator inhibitor 1 in the subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…Human gene LEP codes for leptin, which is also called obesity hormone because laboratory animals with a protein-damaging mutation in this gene are abnormally obese [119], as shown in Table 5. As readers can see in this table, within the human leptin promoter, we identified two unannotated SNPs able to cause obesity that can accelerate atherogenesis in line with a review article [120] found in PubMed using its keyword search utility [38]. In addition, here we found three unannotated SNPs increasing the LEP level (and thus protecting against both obesity and atherosclerosis [121]) as candidate SNP markers of an atherogenesis slowdown (e.g., rs34104384, Table 5).…”
Section: Human Genes Associated With Obesitysupporting
confidence: 70%
See 1 more Smart Citation
“…Human gene LEP codes for leptin, which is also called obesity hormone because laboratory animals with a protein-damaging mutation in this gene are abnormally obese [119], as shown in Table 5. As readers can see in this table, within the human leptin promoter, we identified two unannotated SNPs able to cause obesity that can accelerate atherogenesis in line with a review article [120] found in PubMed using its keyword search utility [38]. In addition, here we found three unannotated SNPs increasing the LEP level (and thus protecting against both obesity and atherosclerosis [121]) as candidate SNP markers of an atherogenesis slowdown (e.g., rs34104384, Table 5).…”
Section: Human Genes Associated With Obesitysupporting
confidence: 70%
“…Human gene APOA1 for apolipoprotein A1 carries a known SNP marker (APOA1:−35A>C) of hematuria, fatty liver, and obesity [122], and is a commonly accepted risk factor of atherogenesis acceleration [120]. Indeed, this prediction is consistent with the outcome of treatment of atherosclerosis using exogenous apolipoprotein A1 [123] as well as by both a low-protein diet and exercise increasing the endogenous APOA1 level in obese post-menopausal women [124].…”
Section: Human Genes Associated With Obesitymentioning
confidence: 75%
“…A recent study indicated that excessive gain of gestational weight, gestational diabetes mellitus, breast feeding for a period of less than 6 months, and hypertensive disorders of pregnancy may lead to maternal and childhood obesity [2]. Skrypnik et al [3] presented the current state of knowledge about the genetic basis of obesity complications. Early attention and detection of these risk factors may prevent the development of obesity and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Reported lifestyle factors include alcohol consumption, smoking [18,19] and physical inactivity [20]. The role of genetic factors in determining BMI has also been extensively reported in the literature [21,22]. Several cross-sectional and longitudinal studies in non-African countries have also observed a positive association between BMI and pesticide exposure [2327].…”
Section: Introductionmentioning
confidence: 99%